The legislation of democratic management in the state education network in Rio Grande do Norte: What is the manager's role? (Revista Contexto & Educação, 2023)
Abstract: The text presents a reflection on the role of the management team in the state schools of Rio Grande do Norte, from the Complementary Law no. 585, December 30, 2016. The methodology developed was based on bibliographic and documentary research, which contributed to the understanding of the main systematizations present in the Complementary Law established in the context of the Rio Grande do Norte State Education Network. As results, it was possible to realize that through the legislation sanctioned by the state government: a) the management team of the state schools is composed of the principal, vice principal, pedagogical coordinator and administrative-financial coordinator; b) there are many attributions for the development of daily activities, which present challenges to the school dynamics; c) there is still no democratization in the choice of the pedagogical coordinator and the administrative-financial coordinator, because these are designated by the elected director; and, finally, d) there are contradictions in the Complementary Law when it signals democratic management as a conception of school management, but does not democratize all the processes of choice for the school community.